2019
DOI: 10.1371/journal.pone.0226907
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gut microbiota manipulation with antibiotics on colon tumorigenesis in a murine model

Abstract: It has been suggested that manipulation of gut microbiota using antibiotics can inhibit colitis-associated colorectal cancer (CAC) in a mouse model. We investigated whether timing of gut microbial manipulation using antibiotics affects colon tumorigenesis in the azoxymethane (AOM)/dextran sodium sulfate (DSS)-induced CAC model. CAC was induced in C57BL/6 mice by injection of 12.5 mg/kg AOM followed by three rounds of 1.7% DSS exposure. There were six groups based on timing of antibiotic administration. Colonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Bullman et al showed that the treatment with metronidazole of mice xenografted with CRC decreased both the load of F. nucleatum and the growth of the tumor [79]. In an azoxymethane (AOM)/dextran sodium sulfate (DSS)-induced CRC murine model the alteration of gut microbiota using antibiotics attenuated colon tumorigenesis, but only when gut microbial changes were maintained throughout the entire period of inflammation [80]. Recently, Ma et al described that the alterations of gut microbiota after antibiotic use could contribute to the long-term dysregulation of host immune homeostasis and affect CRC pathogenesis [81].…”
Section: Antibiotic-microbiome Link and Crc Riskmentioning
confidence: 99%
“…Bullman et al showed that the treatment with metronidazole of mice xenografted with CRC decreased both the load of F. nucleatum and the growth of the tumor [79]. In an azoxymethane (AOM)/dextran sodium sulfate (DSS)-induced CRC murine model the alteration of gut microbiota using antibiotics attenuated colon tumorigenesis, but only when gut microbial changes were maintained throughout the entire period of inflammation [80]. Recently, Ma et al described that the alterations of gut microbiota after antibiotic use could contribute to the long-term dysregulation of host immune homeostasis and affect CRC pathogenesis [81].…”
Section: Antibiotic-microbiome Link and Crc Riskmentioning
confidence: 99%
“…The development of CRC has been associated with an overall reduction in microbial diversity ( 145 ) and specific enrichment of individual bacteria such as Fusobacterium nucleatum ( 146 ) and loss of potentially protective bacteria such as Roseburia ( 147 ). Dysregulation of the gut microbiome in inflammatory disease may affect CRC development as colonic tumorigenesis was observed to be attenuated by antibiotics in a mouse model of colitis induced CRC ( 148 ). These associative studies have generated many questions and much interest with regard to causative links between the microbiome and the generation of CRC and the potential of the microbiome to provide biomarkers or prognostic indicators for CRC.…”
Section: Sexual Dimorphism and The Tumor Microenvironment In Crcmentioning
confidence: 99%
“…Recently, it was shown that Apc Min/+ mice receiving the fecal samples from CRC patients develop increased number of intestinal adenomas and a more advanced tumor development compared with those receiving fecal samples from healthy subjects [ 8 ]. In a colitis-associated CRC mouse model chemically induced by azoxymethane (AOM) and dextran sodium sulfate (DSS), antibiotic treatment significantly decreases the number, the size and the histological score of the colonic tumors [ 9 ]. Furthermore, transfer of fecal samples from patients with CRC enhances intestinal cell proliferation in germ-free mice and promotes tumor formation in conventional mice that were pre-treated with antibiotics and then with AOM [ 10 ].…”
Section: Introductionmentioning
confidence: 99%